Multicomorbidity of chronic diseases and substance use disorders and their association with hospitalization: Results from electronic health records data. (1st November 2018) - Wu, Li-Tzy; Zhu, He; Ghitza, Udi E.
Highlights: Comorbidities of substance use disorders (SUDs) and chronic diseases were examined. In the sample (N = 211, 880), 48.3% had at least 1 of 9 chronic conditions examined. The prevalence of any SUD (13.3%) increased with the number of comorbidities. Hospitalization was more prevalent among patients with SUD than those without it. Regardless of comorbidity, SUD was associated with elevated odds of hospitalization. Abstract: Background: Chronic diseases are prevalent and the leading causes of mortality. Comorbidity of substance use disorders (SUDs) and chronic diseases is understudied to inform behavioral healthcare integration. Objectives: This study leveraged electronic health record (EHR) data of 211, 880 adults from a large health system to examine prevalence and correlates of comorbidity of SUDs and nine chronic disease groups and to determine their association with hospitalization. Methods: Logistic regression analyses were conducted to estimate associations between chronic diseases and SUDs. To control for severity of diagnosis, analyses of associations between SUD and hospitalization were stratified by the number of chronic conditions. Results: In the sample, 48.3% had ≥1 chronic condition (hypertension 33.7%, arthritis 16.2%, diabetes 13.7%, chronic kidney disease 9.9%, asthma 9.1%, chronic obstructive pulmonary disease 8.9%, ischemic heart disease 8.3%, cancer 4.6%, and hepatitis 1.3%). Prevalence of SUD (overall 13.3%) among patients increased with multiple chronic conditions (14.3% having SUD among patients with one condition; 21.2% having SUD among patients with two to three conditions; and 32.5% having SUD among patients with 4–9 conditions). Chronic conditions were associated with increased odds of SUDs. For all SUD groups, hospitalization was more prevalent among patients with SUD than those without it; prevalence of hospitalization increased with the number of comorbid chronic conditions. Conclusions: Findings reveal a striking pattern of multicomorbidity of SUD and chronic diseases and its positive association with hospitalization. Behavioral healthcare integration should consider efforts to assess and treat comorbid SUD and chronic diseases, especially among adults with multiple chronic conditions.